Perlindungan Hukum Terhadap Pemegang Saham Minoritas Dalam Proses Merger Bank Perkreditan Rakyat - Komang Krisna Yustika Putra; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Warmadewa Press, 2025)
The banking sector has a very strategic function in all activities to bring together society and become a channel for people's lives again in various forms, one of which is an effort to provide support and development of the national economy. The general meeting of shareholders of the GMS is related to mergers and how legal protection is for minority shareholders in determining the fair price of shares. The author uses normative legal research. The conclusions are: First, the position of minority shareholders in the implementation of the GMS related to the merger process in a BPR is in a weak position when compared to the position of the majority shareholder. In the merger process which is based on the number of quorums as stated in Article 89 of the PT Law which states that if a GMS is related to a merger, it is required to have a requirement of at least ¾ of the total number of shares. Second, in Article 13 POJK is one of the requests to BPRs for their shares to be purchased at a fair price, but the regulation does not clearly say that Minority Shareholders can also file a lawsuit if they feel they have been disadvantaged by the merger process.